PRDX6 Drives Breast Cancer Progression Through Mitochondrial Biosynthesis and Oxidative Phosphorylation - Mei Dai; Danhua Zhang (Cancer Medicine, 2025)
ABSTRACT Background Peroxiredoxin 6 (PRDX6) scavenges reactive oxygen species (ROS) and plays a key role in antioxidant defense. Although PRDX6 is involved in various cancers, its role in breast cancer (BRCA) remains unclear. Methods Cell proliferation was assessed using CCK‐8, EdU staining, and colony formation assays. Migration and invasion were evaluated via wound‐healing and transwell assays. ROS levels and mitochondrial membrane potential were measured by fluorescence microscopy or flow cytometry. Oxidative phosphorylation (OXPHOS) activity was determined by ATP production and NAD+/NADH ratio. Mitochondria were visualized by TEM, and mitochondrial complex subunits were detected by quantitative real‐time PCR and Western blotting. In vivo effects were evaluated using a xenograft tumor model. Results Although PRDX6 was downregulated in BRCA overall, it showed elevated expression in aggressive subtypes and advanced‐stage tumors, correlating with poor prognosis. Overexpression of PRDX6 enhanced BRCA cell proliferation, migration, and invasion. PRDX6 reduced ROS levels, upregulated mitochondrial transcription factor A (TFAM) expression, and promoted mitochondrial complex subunit expression and OXPHOS. Inhibition of TFAM led to a decrease in the expression of some of the mitochondrial complex subunits, which reversed the pro‐carcinogenic phenotype of the tumor. PRDX6 also promoted tumor growth in vivo. Conclusion PRDX6 maintains intracellular homeostasis by reducing ROS and promotes mitochondrial biogenesis and OXPHOS through TFAM‐dependent and ‐independent pathways, driving BRCA progression.